Manfaat Partisipasi Masyarakat dalam Program Pengelolaan Sampah - Adi Chandra Berampu; Ivanovich Agusta (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2015)
The existence of the company in a public area should be able to bring benefits to society itself, as in the social, economic, and environmental. To realize these expectations then CSR programs are implemented by taking into account the participation of the community and other stakeholders, because participation is one of the the most important of community development principles. There are internal factors that considered relates to the level of participation. Variables of internal factor (individual characteristics) are age level, education level, length of stay, and income level. The results of the research showed that there is no relationship between the individual characteristics to the level of community participation. The level of community participation considered relates to the level of program’s benefits that can be felt. Variables of program utilization such as the level knowledge level, skill level, environmental cleanliness level, and economic opportunities level. The results of the research showed that there is a relationship between the level of participation and the level of program’s benefits that community receive.Keywords: individual characteristics, the participation level, the program’s benefits level, waste management